Some haematological parameters in partridges (allectoris gracea) bred in konya - Ercan Keskin; Ramazan Çöl; Tufan Keçeci; Hüdai İpek; Feyyaz Önder (Eurasian Journal of Veterinary Sciences)
This study was conducted to determine of some haematological parameters in partridges (Alİectoris gracea) which were bred in Konya region. The healthy 80 patridges which were different age and sex were used as material in the investigation. The blood samples were taken by cardiac puncture. In this investigation, red blood cell counts (BBC), haemoglobin concentrations (Hb). haematocnt values (Hmt) and white blood cell counts (WBC) of male and female chicks were found to be 2.87x106 /mm3, 10.15 g/dl. 34,23 %, 19.50x103 /mm3 and 2.49x106 /mm3, 10.30 g/dl, 33.00 %, 19.25x103 /mm3, respectively The same values of male and lemale young patridges were determined to be 2.15x106 / mm3, 11,08 g/dl, 32.20 %, 20.00x103/mm3 and 2,04x106 /mm3, 10,91 g/dl, 35.00 %. 23.83x103 /mm3, respectively. Furthermore. these parameters of adult male and female palridges were found to be 2.19x106 /mm3, 11.72 g/dl, 36.20 %, 20.80x103 /mm3 and 2.23x106 /mm3. 10.57 g/dl. 34.00 %. 21,00x103/mm3, respectively. In general, there were no Significant differences in the investigated parameters between male and female partridges. On the other hand, although the white blood cell count, mean corpuscular volume and mean corpuscular hemoglobin of the chicks and the lymphocyte percentage of the adult were lower. Ihe red blood cell count of the chicks was higher amount when compared to the same values of young partridges. In addition, while the basophil percentage of adults was higher, the monocyte percentage was lower than other groups. Based on results, it was concluded thai some haematological values were influenced by age differences of Ihe patridges and the data obtained in the study could be useful to establish some baseline values about haematological parameters in the different ages of male and lemale partridges.